The impact of digital marketing and marketing psychology on amanda sweet kokona UMKM product purchase decisions in the city of Bandung - Andhi Sukma; Muhamad Fauzi Hilman Nadhif (Institute of Computer Science (IOCS), 2023)
A descriptive quantitative research methodology was adopted. All of the students in the city of Bandung were the sampled population for this study. All students in the city of Bandung were randomly selected as part of the sampling procedure for this study. Multiple linear regression analysis with a significance threshold of 5% or 0.05 was the technique used for data analysis. The SPSS ver. 25 programs were used to analyze the whole investigation. With a significance value of 0.323> 0.05, a t-count value of 0.994 t>, and a t-table value of 1.664, it was demonstrated in this study that marketing psychology variables did not substantially affect purchasing decisions for items Amanda Sweet Kokona Drinking Chocolate in Bandung City.